Subversion of host kinases: a key network in cellular signaling hijacked by Helicobacter pylori CagA - Tegtmeyer, Nicole; Neddermann, Matthias; Asche, Carmen Isabell; Backert, Steffen (Molecular Microbiology, 2017)
Helicobacter pylori is a paradigm of persistent pathogens and major risk factor for developing severe diseases including adenocarcinoma in the human stomach. An important bacterial factor linked to gastric disease progression is the cag pathogenicity island-encoded type-IV secretion system (T4SS) effector protein CagA. Translocated CagA undergoes tyrosine phosphorylation at EPIYA-motifs and then activates or inactivates multiple host signaling proteins in a phosphorylation-dependent and phosphorylation-independent fashion. In this way, intracellular CagA acts as a ‘masterkey’ or ‘picklock’, which evolved during evolution to hijack key host cell signal transduction functions. Crucial targets of CagA represent a variety of serine/threonine and tyrosine kinases, which control major checkpoints of eukaryotic signaling. Here we review the signal transmission by translocated CagA on multiple receptor kinases (c-Met and EGFR) and non-receptor kinases (Src, Abl, Csk, aPKC, Par1, PI3K, Akt, FAK, GSK-3, JAK, PAK1, PAK2 and MAP kinases), manipulating a selection of fundamental processes in the human gastric epithelium such as cell adhesion, polarity, proliferation, motility, receptor endocytosis, cytoskeletal rearrangements, apoptosis, inflammation and cell cycle progression. This enormous complexity generates a highly remarkable and puzzling scenario during H. pylori infection. The contribution of these signaling pathways to bacterial survival, persistence and gastric pathogenesis is discussed.
Created from Fastlane, Scopus look-up